Comparison of intrathecal morphine and epidural bupivacaine analgesia for post operative analgesia after elective abdominal hysterectomy - Nayan, Anafairos Md (2016)
Abstract Background: Epidural bupivacaine (EB) a common analgesia technique after abdominal hysterectomy. However, this technique is invasive and requires catheter placement in epidural space. Intrathecal morphine (ITM) is another potential technique which is less invasive and requires only single injection. The aim of this study was to compare postoperative analgesia effectiveness between these two techniques. Methods: 32 patients who underwent elective abdominal hysterectomy were randomised into two groups; Group ITM (ITM 0.2 mg + 2.5ml 0.5% bupivacaine) (n=16) and Group EB (0.25% bupivacaine bolus + continuous infusion of 0.1% bupivacaine + fentanyl 2 μg/ml) (n=16). The procedure was done prior to induction and all patients subsequently received standard general anaesthesia. Both groups were provided patient controlled analgesia (PCA) morphine as rescue analgesia. Pain assessment was done at first hour post-operative then fourhourly up to 24 hours using visual analogue scale (VAS). Total morphine consumption, length of stay, time to early mobilization and time for first patient controlled analgesia (PCA) morphine demand were also recorded. Results: ITM showed significantly lower median of VAS than EB after 1st hour [1.00(IqR 1.00) vs. 3.00(IqR 3.00), p<0.001], 8th hour [1.00(IqR 1.00) vs. 2.00(IqR 1.00), p=0.018] and 16th hour [1.00(IqR 1.00) vs. (1.00(IqR 1.00), p=0.006] of surgery. The mean VAS at 4th hour was also significantly lower in ITM [1.81(1.17) vs. 2.88(1.41), p=0.027]. Total morphine consumption [11.31(6.56) vs. 16.50(4.80) mg, p=0.016] and time for early mobilization [2.06 (0.25) vs. 2.63(0.89) days, p=0.025] were also significantly less in ITM. Otherwise, there were no significant differences in length of stay, PCA demand time and side effects. Conclusions: ITM was better post-operative analgesia, required lesser rescue analgesia and shorter time for early mobilisation than EB in abdominal hysterectomy surgery